2012
DOI: 10.1353/pla.2012.0015
|View full text |Cite
|
Sign up to set email alerts
|

What Liaisons Say about Themselves and What Faculty Say about Their Liaisons, a U.S. Survey

Abstract: AcknowledgmentsThe authors thank all of the survey participants for taking the time to answer our questions. We thank Dr. Donald Dilmore for providing a copy of the questionnaire used in his research. The authors also thank Jeanne Cross, P. Mckraken, Bob, "rat a tat natty," and the other friends and colleagues who looked at drafts of our survey questionnaire and suggested improvements to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Many of the faculties feel that, it is a time consuming process and hardly intends to participate in it 14 . Even faculties rarely glance through a recommended list unless it is being consistently followed up and pursued by the librarian and also the relation between faculty and librarian play a great role 16,16 .…”
Section: Collection Development Practices and Problems In Indian Academmentioning
confidence: 99%
“…Many of the faculties feel that, it is a time consuming process and hardly intends to participate in it 14 . Even faculties rarely glance through a recommended list unless it is being consistently followed up and pursued by the librarian and also the relation between faculty and librarian play a great role 16,16 .…”
Section: Collection Development Practices and Problems In Indian Academmentioning
confidence: 99%
“…In order for the services they offered to their departments to be successful, subject librarians had to find the most successful ways to communicate with them. A study by Arendt and Lotts (2012) found that the main methods used by their respondents to communicate with faculty were email, face-to-face communication and telephone calls. This study found that emails and telephone calls were the most used methods of communication, while face-to-face meetings were used by less than 50% of the respondents, probably because faculty were often out of their offices, conducting classes.…”
Section: Responsibilitiesmentioning
confidence: 99%
“…Julie Arendt and Megan Lotts conclude that disciplinary faculty who were in frequent and personal contact with their librarian liaison were most likely to report that they were "satisfied" or "very satisfied" with the liaison's performance. 112 Successful connections between library and disciplinary faculty create opportunities for long-term collaborations. As new disciplinary faculty mature as researchers and earn tenure, they will see the value added by their relationship with librarians in general and librarians with faculty status in particular.…”
Section: May 2014mentioning
confidence: 99%